Optimization for continuous overflow proteolytic hydrolysis of spent brewer’s yeast by using proteases - Ngoc, Nguyen Thi Thanh; Ha, Quan Le; Thuan, Dinh Van (Vietnam Journal of Biotechnology, 2018)
A large amount of spent yeast as by-product is annually generated from brewing industry and it contains about 50-55% protein with good balance of amino acids. The hydrolysate produced from spent brewer’s yeast may be used in food application. The yield of proteolylic hydrolysis for spent brewer’s yeast and amino acid contents of hydrolysates depend on factors such as temperature, pH value, type of used enzyme and ratio enzyme/substrate, time. Besides, applied hydrolysing methods (batch-, or continuous method) has effected on degree of hydrolysis. With the purpose of how proteolytic hydrolysis having effects on the spent brewer’s yeast for food application in industrial scale, continuous overflow method was used in this study. Bitterness of hydrolysate and the yield of continuous overflow proteolytic hydrolysis process are the two interested factors for protein hydrolysis. In this report, it is dealt with determination for optimal conditions to obtain the highest yield of hydrolysis process and the lowest bitterness of hydrolysate. Response surface methodology (RSM) was used to determine optimal condition for continuous overflow proteolytic hydrolysis of spent brewer’s yeast. The optimal conditions for obtaining high degree of hydrolysis and low bitterness are determined as followings: ratio of enzyme mixture (alcalase 7.5 U/g and flavourzyme 10 U/g), pH at 7.5, hydrolysis temperature at 51oC and hydrolysis time of 9 hours. Under the optimal conditions, the yield of hydrolysis was 59.62% ± 0.027 and the bitterness equivalently with concentration of quinine was 7.86 ± 0.033 μmol /ml